2017
DOI: 10.1515/fv-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Hepatitis E Virus in Domestic Pigs

Abstract: Hepatitis E virus (HEV) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Unfortunately, the HEV genotypes could not be identified because the short RT-PCR product (85 bp) was not suitable for genotype analysis. However, the detection of HEV RNA with a high detection rate in monkey faeces, even higher than that reported in pigs, the primary reservoir [ 34 36 ], can be used as a preliminary information that warrants a further investigation to conclude that monkey faeces are a source of HEV.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the HEV genotypes could not be identified because the short RT-PCR product (85 bp) was not suitable for genotype analysis. However, the detection of HEV RNA with a high detection rate in monkey faeces, even higher than that reported in pigs, the primary reservoir [ 34 36 ], can be used as a preliminary information that warrants a further investigation to conclude that monkey faeces are a source of HEV.…”
Section: Discussionmentioning
confidence: 99%
“…In Slovakia, infection was detected for the first time in animals only in 2017, when Jackova et al, published on the prevalence of hepatitis E virus in the domestic pigs. RT-PCR analysis of 269 enteric samples revealed that 32 pigs (11.9%) of all age categories were HEV RNA positive [ 27 ]. Moreover, to date only 83 cases of autochthonous disease in humans have been officially reported.…”
Section: Discussionmentioning
confidence: 99%